Teacher-Student Interaction Patterns in Aqidah Akhlaq Instruction - Umar, Muallief; Rosyidah, Binti; Sholikah, Dewi Titik (IERA, Islamic Education and Research Academy, 2023)
This research aims to describe teacher interaction patterns in Aqidah Akhlaq learning, Describe the direction/guidance of Islamic religious lessons for educators in communicating in learning Aqidah Akhlaq, To describe the supporting and inhibiting factors for teacher interaction in learning Aqidah Akhlaq. This research uses a qualitative descriptive approach, the data obtained was carried out by means of interviews, interviews and documentation. The findings of this research show that the teacher's interaction pattern in learning aqidah akhlaq aims to introduce and familiarize students with learning material about aqidah akhlaq. The guidance of Islamic teachings for teachers is a teacher who has sincere motivation to teach, is sincere in applying his knowledge, and acts as a loving parent. There are several supporting factors. These supporting factors are learning materials that teachers can master, teaching and learning programs that can be managed well, being able to use learning tools/media and managing the class.